Dampak Jumlah Plasticizer dalam Nilai Kekerasan Plastik PVC - Manurung, Meilani Mandhalena; Leksonowati, Nur Fitria Pujo; Pamungkas, Nurman; Stefani, Windy; Batubara, Ninda Hardina; Purba, Adi Syahputra (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
This paper provides a detailed investigation into the effects of Trioctyl Trimellitate (TOTM) plasticizer levels on the hardness of Polyvinyl Chloride (PVC) materials. The study reveals an inverse correlation between the level of TOTM plasticizer and the hardness of PVC, with an increase in TOTM levels leading to a decrease in hardness. This trend is consistent across various PVC samples, despite minor variations. The role of plasticizers in determining the physical and mechanical properties of PVC is further explored, emphasizing their function in reducing PVC's crystallinity, thereby producing a clearer and more flexible material. This research contributes to the understanding of how plasticizers can be used to tailor the properties of PVC, leading to the development of two distinct types of PVC: Flexible PVC, which contains a plasticizer, and Rigid PVC, which does not. The findings underscore the importance of plasticizers in material design and engineering, offering valuable insights for future applications.